Where does public funding for HIV prevention go to? The case of condoms versus microbicides and vaccines - Scharf Maja; Peters Anny JTP; van Driel Francien TM; Jansen Willy HM (BMC, 2010)
Abstract This study analyses the priorities of public donors in funding HIV prevention by either integrated condom programming or HIV preventive microbicides and vaccines in the period between 2000 and 2008. It further compares the public funding investments of the USA government and European governments, including the EU, as we expect the two groups to invest differently in HIV prevention options, because their policies on sexual and reproductive health and rights are different. We use two existing officially UN endorsed databases to compare the public donor funding streams for HIV prevention of these two distinct contributors. In the period 2000-2008, the relative share of public funding for integrated condom programming dropped significantly, while that for research on vaccines and microbicides increased. The European public donors gave a larger share to condom programming than the United States, but exhibited a similar downward trend in favour of funding research on vaccines and microbicides. Both public donor parties invested progressively more in research on vaccines and microbicides rather than addressing the shortage of condoms and improving access to integrated condom programming in developing countries.